COMBINATION OF INTERNET OF THINGS AND THEORY OF CONSTRAINTS FOR ENHANCING COMPANY’S PERFORMANCE EFFICIENCY - SEMENENKO, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The theory of constraints is an important tool in modern management that enables companies to effectively manage their resources and processes to achieve strategic goals. At the core of this theory lies the recognition that every system or process has constraints that limit overall productivity and efficiency. The application of the theory of constraints requires analyzing the system as a whole, focusing on identifying and eliminating the key constraints that hinder achieving optimal productivity. The Internet of Things (IoT) involves connecting various devices to the Internet, enabling the collection, processing, and analysis of vast amounts of data to improve various aspects of company operations. In the business context, the use of IoT opens up numerous opportunities for enhancing efficiency and optimizing processes. This includes automation of production, improvement of logistics, detection of technical equipment problems through sensors, and much more. The use of digital technologies, particularly the Internet of Things (IoT), creates prospects for enhancing the efficiency of company operations in various business sectors. One promising approach is the combination of IoT with the theory of constraints, allowing for the identification and elimination of production process constraints, optimization of inventory management and logistics, as well as enhancing the quality and efficiency of overall business management. This article examines the combination of IoT and the theory of constraints in the context of enhancing company performance efficiency. It discusses methods and strategies for implementing these technologies, their potential applications, and innovative uses in various business sectors. The main focus is on analyzing the implementation of IoT and the theory of constraints in practice, as well as identifying optimal strategies for improving operational efficiency in business. A systematic analysis of the impact of combining IoT and the theory of constraints on company performance efficiency is conducted, detailing optimization and management processes, as well as identifying key success factors in the implementation of these technologies.